Microbiological quality of salmon (Salmo salar) sold in cities of the state of São Paulo, Brazil - Nespolo, Natália Maramarque [UNESP]; Martineli, Thaís Mioto [UNESP]; Rossi Jr., Oswaldo Durival [UNESP] (Sociedade Brasileira de Microbiologia, 2012)
The present paper evaluated the microbiology of salmon by quantifying mesophilic heterotrophic microorganisms, total and thermotolerant coliforms, and the presence of Vibrio parahaemolyticus, Staphylococcus aureus, Salmonella sp., Escherichia coli and Aeromonas sp. in the meat. This study can provide technical support for the suggestion of a new regulation of a Brazilian legislation through specific microbiological standards concerning the consumption of raw fish. A number of 31 (16 cooled and 15 frozen) samples of salmon were collected in the retail market network of a few cities in the State of São Paulo, Brazil. Results presented populations of mesophilic heterotrophic microorganisms ranging from 1.0 x 10 and 3.9 x 10(6) CFU/g, total and thermotolerant coliforms in 32.25% and 19.35% of the samples, respectively, and Aeromonas sp. in 41.95% of the samples with a populational variation ranging from 2.0 x 10² to 8.0 x 10³ CFU/g. Staphylococcus aureus was found in one sample whereas Vibrio parahaemolyticus, Salmonella sp. and Escherichia coli were not found. These results demonstrated the presence of potencially pathogenic microorganisms in fresh fish consumed in Brazil, highlighting the necessity of control measures to avoid public health problems related to the consumption of raw fish.
Keywords: fish; salmon; microbiology; pathogenic bacteria